Racialized Appetites in Four Girls at Cottage City, Malinda Russell's Domestic Cook Book, and Southern Soufflé. - Mann, Molly (Iowa Journal of Cultural Studies)
Emma Dunham Kelley-Hawkins' novel Four Girls at Cottage City (1898), Malinda Russell's Domestic Cook Book: Containing a Careful Selection of Useful Receipts for the Kitchen (1866), and Erika Council's food blog Southern Soufflé (2012-present) are texts that differ in form, genre, purpose, and period. Read together, these works, all three of which have received relatively little critical attention, however, help piece together a historical and cultural framework for contemporary views of Black women, food and professionalized labor, a subject which itself has received less attention, critically, than white women and the professionalism of their domestic labors. The three exemplary works that are the focus of this essay all resist an embodied racial logic that would categorize and value various forms of women's domestic labor according to the bodies that perform it. Through their writing, Kelley-Hawkins, Russell, and Council engage questions of who consumes and who is consumed within the context of U.S. cultural history and its long-held, violently deployed misunderstanding of race.